Simangambat, Candi Hindu di Sumatera Utara - Eka Asih P. Taim (Berkala Arkeologi Sangkhakala, 2010)
AbstractSimangambat temple was reported by Schnitger, a Dutch Scholar, in 1935. At that time Simangambat was already became a brick ruins, some of sandstones were bare a very beautiful relief. In 2008 and 2009 a team from National research and development center for archaeology and Medan archaeological office tried to revealed all of things about Simangambat, its architecture, religious, art, and style.